Les défis d’une approche multisource et diachronique de l’occupation du sol : l’exemple de la vallée de la Garonne - Nicolas Poirier (Humanités Numériques)
The history of land use dynamics can only be written by apprehending a long period of time that transcends academic divisions. It is a necessary step to finely perceive the stages of construction of rural spaces by ancient societies. It requires recourse to a variety of information sources. The difficulties of crossing them are mainly due to the blind spots and the variations in scale and precision, both spatial and chronological, that characterise each of them. In this sense, geographic information systems (GIS) can appear as especially relevant tools to ensure the centralisation, analysis and crossing of information. By emphasising spatial input, the rural historian-archaeologist can deploy the whole range of spatial analysis methods provided by geography. These various challenges are illustrated by the presentation of the first results of the REPERAGE program, which aims to reconstruct the dynamics of the landscape and settlement in the Garonne valley.